Gambaran sikap terhadap kesehatan dan label produk pangan pada mahasiswa jenjang sarjana program studi gizi di Kepualauan Riau - Rosyidah, Haqqelni Nur; Made Tantra wirakesuma; Ayu Rosanti (Pusat Riset dan Inovasi Nasional, 2023)
Obesity in adolescents and adults is a phenomenon of particular concern from a health perspective. There have been several attempts to reduce obesity, one of which is by controlling food calorie intake. Food calories can be informed through food labels on food products. Food labels are a source of information or media knowledge about food for consideration in buying a product. Consumer awareness in reading food labels before buying or consuming a food product is still very low. This study aims to describe the awareness or attitude of nutrition students towards health and food product labels. The research method is observational with a cross sectional design. The results of the study 53.1% of respondents have a negative attitude towards health and food product labels.